Förstudie om förebyggande underhåll - Lam, Diana; Jovic, Emilia (My University, 2026)
Skanska Industrial Solutions produces asphalt and supplies the Nordic road network with high-quality paving materials. Since asphalt is a perishable product that must be delivered within a limited timeframe, production places high demands on efficiency. To ensure smooth and uninterrupted operations, regular maintenance is essential. A recurring challenge is that maintenance work is often carried out too late due to limited resources and an insufficiently structured workflow. This makes it difficult to anticipate deviations and results in a more reactive and costly approach. The aim of this thesis was to examine how Skanska Industrial Solutions can implement preventive maintenance to strengthen its operations. Data collection included literature reviews and interviews, along with benchmarking across companies from different industries. This approach provided broader insights and multiple perspectives on how maintenance activities can be managed effectively. The findings indicate that shortcomings in maintenance are primarily caused by organizational rather than technical factors. While practical knowledge exists, it is not prioritized. Maintenance practices are largely dependent on individuals and based on experience, meaning that a clear and standardized structure is lacking. The challenges stem from insufficient training, education, engagement, and involvement. Over time, the existing way of working has remained largely unchanged, highlighting a clear need for improvement. The report presents recommendations on how current practices can be developed and how new measures can be introduced to improve preventive maintenance